Augmentation enterocystoplasty in a polytrauma dog with extensive bladder necrosis. Issue 2 (3rd May 2021) - Gonçalves, Ronald; Wade, Jennifer; Fransson, Boel; Ngwenyama, Thandeka
Abstract: An 11‐year‐old male castrated Terrier was referred for multiple pelvic fractures following vehicular trauma. Pertinent clinical findings included a painful abdomen, non‐ambulatory paraparesis, absent anal tone and perineal reflex and urinary incontinence. Relevant findings on abdominal CT were pelvic fractures, prepubic tendon avulsion and retroflexed urinary bladder. A urinary catheter was placed to decompress the bladder, and a positive contrast cystourethrogram showed no evidence of leakage. Intraoperatively, it was found that approximately 90% of the bladder was necrotic; both ureters, prostatic urethra and the sphincter appeared viable. An enterocystoplasty was performed using a vascularized jejunal segment, made into an enteric pouch, and sutured to the remainder of the viable bladder. Ureteral partial obstruction, oliguria and UTI were short‐term complications; the patient also had persistent urinary incontinence. Enterocystoplasty is a surgical procedure that can be considered in patients with extensive bladder necrosis after carefully considering the possible short and long‐term complications.